Understanding earnings of creative graduates: rip-off University degrees or under-rewarded careers? - Brook, Orian (International Journal of Population Data Science, 2025)
This research aimed to understand the low incomes of creative graduates, which were reported in recent analysis of earnings data, which had inspired a "Crackdown on rip-off university degrees" by the previous government. I planned to explore the variations in earnings according to industry destinations, socio-economic background and educational factors. This research used the Longitudinal Educational Outcomes dataset, joining school and university data with family background and earnings, including both PAYE and freelance income, according to industry, type and region of employer. Using a cross-classified multilevel model I compared the variance in earnings explained by subject studied, HE institution, individual and employment characteristics. Observing the distribution of earnings, rather than just the mean, and the employment dynamics of movements by graduates between different industries, provided further insight. Modelled predictions naive of the subject studies were compared to creative graduates observed earnings to understand the "creative penalty" for different groups. Creative graduates are less likely to be economically inactive than graduates of other subjects 10 years after graduation. Industry of employment, rather than subject studied, explains the largest variance in graduate earnings. The creative penalty, the gap between earnings for graduates in creative compared to other subjects, is largest for men graduating from high tariff institutions, and is relatively small for those graduating from lower tariff institutions, women, and those from less privileged socio-economic backgrounds. Creative graduates are most likely to work in education, creative industries and specialist manufacturing, wholesaling and retail. Lower earnings are found for those working freelance and in multiple jobs, both of which are highly prevalent in creative work. On average, the earnings for creative graduates are lower than other subjects, but with considerable variation. Industry of employment better explains earnings than subject studied. The earnings penalty for creative graduates is much larger in groups who would otherwise be very high earners, whereas in many groups the difference that a creative degree makes is small.